Decoding Autism Awareness Posters: Small Stories and Visual Grammar in Malaysian Health Campaigns - Maslinda Md Yusof; Mohd Iqbal Ahamat; Yi Ling Lee; Seng Tong Chong; Nur Syafiqah Mohd Shkuri (Universiti Sains Islam Malaysia, 2025)
Al-Azkiyaa - International Journal of Language and Education, Volume 4 Issue 2 Page (27–46)